De la documentation aux Humanités numériques : mettre en ligne un fonds documentaire du XXe siècle - Arnaud Millereux; Vincent Rousseau (Les Cahiers de l'École du Louvre)
The documentation compiled by the Recueil général des monuments sculptés en France pendant le Haut Moyen âge research teams is kept in the Sculpture Department of the Musée du Louvre. There are plans to transform it into a database. This “dematerialisation” requires long and meticulous preparatory work. First, it is necessary to have an overall view of the collection that, moreover, bears witness to the systematic working methods that predate the development of information technology. Then the documents to be digitised must be selected and prepared. Four different methods of putting the documents online using the MediaWiki tool may be envisaged, in the hope of ensuring interoperability between the SATHMA database, which is supplemented by CARE and other heritage databases.